Self-organized nanostructure formation during femtosecond-laser inscription of fiber Bragg gratings - Hnatovsky, Cyril; Grobnic, Dan; Coulas, David; Barnes, Michael; Mihailov, Stephen J (Optics letters, 2017)
Periodic planar nanostructures are found in Type II-IR Bragg gratings produced in SMF-28 fiber by side-illuminating it with infrared femtosecond-laser pulses through a phase mask. The planar nanostructures are aligned perpendicular to the laser polarization, as demonstrated using scanning electron microscopy analysis of cleaved fiber samples. Dark field optical microscopy is employed for real-time monitoring of structural changes occurring inside the fiber during the inscription process.